A modified capacitance model of shunt micro switch based on MEMS technology in actuation mode: simulation and analytical study. (January 2020) - Kurmendra,; Kumar, Rajesh
Abstract: In this paper, a modified mathematical model for capacitance analysis of micro-electro-mechanical switch based on Agarwal's Model has been presented. This model is applicable in the condition when the micro-switch is supplied with electrostatic voltages. Effects of perforated structure and fringe field are accounted for accurate capacitance analysis of the micro-switch. The switch parameters such as thickness of dielectric material and actuation voltage for micro switch have also been considered in the present study. The switch is designed and simulated using COMSOL Multiphysics tool and results obtained through simulations have been validated using MATLAB software. It is found that the results obtained by simulation and mathematical model are in agreement closely for the presented study. This model could be used for evaluation of capacitance in downstate of the micro-switch for symmetric structures.